Mrc1-Dependent Chromatin Compaction Represses DNA Double-Stranded Break Repair by Homologous Recombination Upon Replication Stress - Xing, Poyuan; Dong, Yang; Zhao, Jingyu; Zhou, Zhou; Li, Zhao; Wang, Yu; Li, Mengfei; Zhang, Xinghua; Chen, Xuefeng (Frontiers in Cell and Developmental Biology, 2021)
The coordination of DNA replication and repair is critical for the maintenance of genome stability. It has been shown that the Mrc1-mediated S phase checkpoint inhibits DNA double-stranded break (DSB) repair through homologous recombination (HR). How the replication checkpoint inhibits HR remains only partially understood. Here we show that replication stress induces the suppression of both Sgs1/Dna2- and Exo1-mediated resection pathways in an Mrc1-dependent manner. As a result, the loading of the single-stranded DNA binding factor replication protein A (RPA) and Rad51 and DSB repair by HR were severely impaired under replication stress. Notably, the deletion of MRC1 partially restored the recruitment of resection enzymes, DSB end resection, and the loading of RPA and Rad51. The role of Mrc1 in inhibiting DSB end resection is independent of Csm3, Tof1, or Ctf4. Mechanistically, we reveal that replication stress induces global chromatin compaction in a manner partially dependent on Mrc1, and this chromatin compaction limits the access of chromatin remodeling factors and HR proteins, leading to the suppression of HR. Our study reveals a critical role of the Mrc1-dependent chromatin structure change in coordinating DNA replication and recombination under replication stress.